ANALISA PEMAHAMAN PAJAK E-COMMERCE PADA PEDAGANG ONLINE DIKECAMATAN LOSARI KABUPATEN CIREBON - Anggriyani, Sekar Dahlia; Irawati, Irawati (Jurnal Ilmu Administrasi Publik, 2025)
This study discusses the understanding of e-commerce tax among online traders in Losari District, Cirebon Regency, along with the rapid growth of online transactions since 2017. The study uses a qualitative descriptive approach with a purposive sampling technique to determine credible informants, and analyzes data using the Milles model (Data Reduction, Data Display, and Conclusion Drawing/Verification) and verbatim analysis. The results of the study indicate that online traders in Losari District do not yet have an adequate understanding of e-commerce tax. This is due to limited access to information and the complexity of regulations. To overcome this, it is recommended that there be socialization, education, and special assistance to improve the understanding and tax compliance of online traders.